Determinants of Stock Prices of Basic Materials Sector Manufacturing Companies Listed on The Indonesian Stock Exchange - Indri ARIANI; Devi PERMATASARI (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effects of Return on Assets (ROA), Return on Equity (ROE), Debt to Equity Ratio (DER), and Earnings per Share (EPS) on stock prices of manufacturing companies in the basic materials sector listed on the Indonesia Stock Exchange (IDX) during 2022–2024. A quantitative approach with multiple linear regression was employed. The sample was determined using purposive sampling, resulting in 35 firms observed over three years, for a total of 105 firm-year observations. The study uses secondary data drawn from annual reports published on the official IDX website. This study examines the effects of ROA, ROE, DER, and EPS on the stock prices of basic materials manufacturing issuers listed on the IDX over 2022–2024, using a quantitative approach and multiple linear regression. The model satisfies OLS prerequisites (normal residuals, no multicollinearity or heteroskedasticity, and no autocorrelation after correction), allowing for valid inferential interpretation. The results show that EPS has a positive and significant effect on stock prices, while ROA, ROE, and DER have no significant effect.